2015
DOI: 10.1080/14783363.2015.1055239
|View full text |Cite
|
Sign up to set email alerts
|

Key success factors for quality management implementation: evidence from the public sector

Abstract: The purpose of this paper is to identify the crucial factors for the successful implementation of a quality management/total quality management (TQM) process, particularly in the public sector. The paper adopts an explanatory longitudinal case study, using case research design to support the investigation. The case study consists of three government agencies where the results and outcomes of a quality management programme differed. This programme was launched by a specific ministry in Portugal, linked to organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 50 publications
0
22
0
2
Order By: Relevance
“…Specifically, research has shown that quality schemes in the public sector have been found to improve facility management, reducing costs, staff motivation, moral and satisfaction (Delfgaauw and Dur, 2008; Gutierrez et al , 2009), citizen satisfaction and overall organizational performance (Park and Rainey, 2012; Lakhal et al , 2006). Although there is considerable research material and knowledge concerning the adoption of TQM in the manufacturing environment, there is still a lack of TQM studies in the services sector (Alonso-Almeida et al , 2013) and more specifically in the public services sector (Pimentel and Major, 2015). The literature has noted the lack of a TQM model in several services subsectors, including the public sector, as there is still no appropriate framework for applying TQM specifically in this sector (Jaca and Psomas, 2014; Sit et al , 2011; Al-Tabbaa et al , 2013; Boulter et al , 2013; Calvo-Mora et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, research has shown that quality schemes in the public sector have been found to improve facility management, reducing costs, staff motivation, moral and satisfaction (Delfgaauw and Dur, 2008; Gutierrez et al , 2009), citizen satisfaction and overall organizational performance (Park and Rainey, 2012; Lakhal et al , 2006). Although there is considerable research material and knowledge concerning the adoption of TQM in the manufacturing environment, there is still a lack of TQM studies in the services sector (Alonso-Almeida et al , 2013) and more specifically in the public services sector (Pimentel and Major, 2015). The literature has noted the lack of a TQM model in several services subsectors, including the public sector, as there is still no appropriate framework for applying TQM specifically in this sector (Jaca and Psomas, 2014; Sit et al , 2011; Al-Tabbaa et al , 2013; Boulter et al , 2013; Calvo-Mora et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…El segundo objetivo establece estudiar el papel que juega la adopción por los organismos gestores de la ciudad de CM y de GCT en el desarrollo de DEU. Ambos enfoques de gestión han sido identificados como útiles para ayudar a avanzar hacia una gestión a largo plazo que contemple, de manera holística, los diferentes ámbitos de gestión urbana y los distintos públicos relevantes a los que aportar valor añadido (Boisen et al, 2018;Karyotakis & Moustakis, 2014;Pimentel & Major, 2016;Wiśniewska & Szczepańska, 2014). También se puede investigar la posible relación de estos enfoques de gestión con los resultados urbanos en términos económicos, de forma directa e indirecta, mediante el apoyo a la DEU.…”
Section: La Investigaciónunclassified
“…A aplicação destes programas conferem benefícios à organização, como melhorias dos processos internos, agregação de valor e maior competitividade no mercado (Neves, Maués & Nascimento, 2002e Singh, Power & Chuong, 2011. Porém, as implantações destes programas, por si, nem sempre garantem a melhoria dos processos (Paula et al, 2004;Lo et al, 2013;Pimentel & Majora, 2015).…”
Section: Gerenciamento Pelas Diretrizes E Programa De Qualidadeunclassified